ANALISIS KEEFEKTIFAN DAN TANTANGAN ETIS TERHADAP PERAN AI DALAM MENINGKATKAN PEMBELAJARAN MULTIKULTURAL - Nendissa, Julio Eleazer; Langi , Elsjani Adelin; Pantow, Anita Grays Freidelien; Tonapa, Damaris; Sampepadang, Refail D.P. (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2025)
Multicultural education has a significant role in creating awareness and empathy for cultural diversity in an increasingly heterogeneous society. AI technology offers opportunities to support this education through personalization of learning, data-based analysis of student needs, and provision of culturally relevant content. This article aims to analyze the effectiveness and ethical challenges of implementing AI in multicultural learning. The research method used is a qualitative approach with a literature review technique, which analyzes literature from Google Scholar and Semantic Scholar related to the use of AI in educational contexts. The results of the study indicate that AI can improve students from various cultural backgrounds, facilitate automatic translation, and support more objective assessments. However, the application of AI in education also faces challenges, including the risk of algorithmic bias and data privacy issues. Algorithms that are not inclusive can reinforce cultural stereotypes, while student data collection raises privacy concerns. The conclusion is that AI has great potential in improving multicultural learning, but requires ethical fences and systems that accommodate cultural diversity so that its implementation can be fair and effective.